The importance of being apt: metaphor comprehension in Alzheimer's disease - Roncero, Carlos; de Almeida, Roberto G. (Frontiers in Human Neuroscience, 2014)
We investigated the effect of aptness in the comprehension of copular metaphors (e.g., Lawyers are sharks) by Alzheimer’s Disease (AD) patients. Aptness is the extent to which the vehicle (e.g., shark) captures salient properties of the topic (e.g.,lawyers). A group of AD patients provided interpretations for metaphors that varied both in aptness and familiarity. Compared to healthy controls, AD patients produced worse interpretations, but interpretation ability was related to a metaphor’s aptness rather than to its familiarity level, and patients with superior abstraction ability produced better interpretations. Therefore, the ability to construct figurative interpretations for metaphors is not always diminished in AD patients nor is it dependent only on the novelty level of the expression. We show that Alzheimer’s patients’ capacity to build figurative interpretations for metaphors is related to both item variables, such as aptness, and participant variables, such as abstraction ability.